Labranza en seco para el control de Cyperus rotundus L., en campos de agricultores - Dinarte, Sandra=700 1 Staver, Charles; Aker, Charles; Sarria, Marvin; Martínez, Reynaldo
Sumario (Es)
4 ref.
Keywords: CYPERUS ROTUNDUS; LABRANZA; AGRICULTORES; ESCARDA; NICARAGUA; CONTROL DE MALEZAS